2010
DOI: 10.4061/2010/262604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Exogenous Emulsifier on Performance, Nutrient Metabolism, and Serum Lipid Profile in Broiler Chickens

Abstract: The effects of an exogenous emulsifier, glyceryl polyethylene glycol ricinoleate, on performance and carcass traits of broiler chickens were assessed. The emulsifier was added to the diet at dose rates of 0 (control), 1 (E1) and 2 (E2) % of added fat (saturated palm oil). Live weight gain (P < .07) and feed conversion ratio (P < .05) in 39 days were higher in the E1 dietary group. Gain: ME intake and gain: protein intake during the grower phase improved quadratically (P < .05). Gross carcass traits were not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
75
4
5

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 15 publications
17
75
4
5
Order By: Relevance
“…The results showed that the addition of emulsifier to the feed significantly increased the ADG and ADFI of chickens for fattening and tended to increase the ADFI of weaned piglets during the entire experimental period, which is in agreement with the findings of previous studies (Xing et al, 2004;Roy et al, 2010;Price et al, 2013). The increased growth and feed intake may be due to certain effects of the dietary emulsifier on pellet quality and fat digestibility (Jones et al, 1992;Roy et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that the addition of emulsifier to the feed significantly increased the ADG and ADFI of chickens for fattening and tended to increase the ADFI of weaned piglets during the entire experimental period, which is in agreement with the findings of previous studies (Xing et al, 2004;Roy et al, 2010;Price et al, 2013). The increased growth and feed intake may be due to certain effects of the dietary emulsifier on pellet quality and fat digestibility (Jones et al, 1992;Roy et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, an increased slaughter yield was also observed in the treated group, suggesting that the relatively rapid growth of the AMT-fed chickens in the grower and finisher phases may have contributed to the comparable increases in carcass and breast muscle yields. The increased growth performance recorded in the present work was probably supported by digestive and physiological mechanisms/processes (Dierick and Decuypere, 2004;Roy et al, 2010); however, these processes were not considered in our experiments. Future studies are in progress to specifically assess the possible improvement of digestibility and fat utilisation.…”
mentioning
confidence: 47%
See 1 more Smart Citation
“…It can also be concluded that increased fat retention by emulsifier during the early stage of life might not be sufficient enough to increase AME N . However, positive effect of emulsifiers on the digestibility of other nutrients has been reported in several studies (Jordan and Weatherup, 1978;Dierick and Decuypere, 2004;Roy et al, 2010). Inoue et al (1977) mentioned that lysolecithins arrange themselves into micelles and liposomes.…”
Section: Discussionmentioning
confidence: 94%
“…Beneficial effect of emulsifiers on N utilisation has been reported by O'Doherty et al (1973), who stated that phospholipids stimulate protein synthesis during active fat absorption. Roy et al (2010) reported that the excretion of N and fat were decreased with the synthetic emulsifier, glycerol polyethylene glycol ricinoleate.…”
Section: Discussionmentioning
confidence: 98%